Bargaining, search, and outside options - Anita Gantner (University of Innsbruck, Department of Public Finance, 2007)
This paper studies a two-sided incomplete information bargaining model between a seller and a buyer. The buyer has an outside option, which is modeled as a sequential search process during which he can also choose to return to bargaining at any time. Two cases considered: In Regime I, both agents have symmetric information about the search parameters. We find that, in contrast to bargaining with complete information, the option to return to bargaining is not redundant in equilibrium. However, the no-delay result still holds. In Regime II, where agents have asymmetric information about the outside option, delay is possible. The solution characterizes the parameters for renegotiation and those for search with no return to the bargaining table.
Keywords: C78; D83; C61; 330; bargaining; two-sided incomplete information; outside option; search; Verhandlungstheorie; Unvollkommene Information; Marktmechanismus; Theorie